The Impact of Marine Ecotourism Development in Rupat Island Indonesia - WARNINGSIH, Trisla; KUSAI, Kusai; BATHARA, Lamun; DEVIASARI, Deviasari (Journal of Environmental Management and Tourism, 2023)
The tourism sector has made considerable contributions to the realization of economic equality, especially among the community living in coastal areas who are highly dependent on marine resources. This research was conducted in July 2022 in the marine ecotourism area of Rupat Island, Riau Province to analyze the impact of developing marine ecotourism on Rupat Island. Primary and secondary data collected through surveys were analyzed using the multiplier effect analysis. The results of the analysis resulted in a Keynesian Income Multiplier value of 1.03, indicating an increase in the income of workers and business owners in the marine ecotourism area of Rupat Island. The increase was to be 1.03 rupiah and with Income Multiplier Type I ratio of 1.07 and Type II ratio of 1.09. It can be taken into conclusion that the tourism activities on Rupat Island bring effects on the local community.